Pengaruh Lingkungan Kerja dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Serta Dampaknya pada Prestasi Kerja di Hotel Inna Garuda Yogyakarta - Hermawan Prasetyo (Media Wisata, 2012)
The purpose of this research was to found both direct or indirect the influence of jobs atmosphere, and leadership style variable toward employee’s performance through job satisfaction at Hotel Inna Garuda Yogyakarta. The data used in this research was primary data which consists of 7 dimensions with 11 indicators for the jobs Atmosphere variable. 5 dimensions with 11 indicators for the Leadership Style variable. 5 dimensions with 11 indicators for satisfaction variable, and 3 dimensions with 11 indicators for job performance variable. The method of collecting data was granted by questionnaires deployment to 70 respondents by quantitative and qualitative descriptive. The result of the data analysis described that all of hypothesis was acceptable. It is indicated that the Corporate Culture, and Leadership Style variable have positively and significantly influenced toward job satisfaction, and based on the result of path analysis ( direct and indirect) that those variables were found directly dominant influenced toward the employee's performance than through the job satisfaction.